Preparation of Polyelectrolyte Complex Films of Chitosan-Alginate Incorporated by Eugenol and its Potency as an Antioxidant Packaging (Jurnal Bahan Alam Terbarukan, 2020)
Preparation of PEC chitosan-alginate films incorporated by eugenol has been investigated. Incorporation of eugenol in chitosan-alginate films was conducted by using the different concentration of eugenol including 0.25% 0.5%, and 1% (% w/v). The effect of eugenol incorporation in chitosan-alginate films was investigated through some properties of the films such as tensile strength, elongation at break, transparency value, and water vapor permeability. Meanwhile, the effectiveness of eugenol incorporation as an active compound of the films was investigated from antioxidant activity of chitosan-alginate films incorporated eugenol. Polyelectrolyte complex (PEC) films of chitosan-alginate was occurred through molecular interaction between polycationic groups of chitosan and polyanionic groups of alginate. The formation of chitosan-alginate PEC films was synthesized at pH ± 4.0. Based on FTIR analysis, the ionic interaction between amine groups (–NH3+) and carboxylate groups (–COO¬) formed strongly. Characterization of films also indicated that PEC films of chitosan-alginate incorporated of eugenol was formed. Study showed that PEC chitosan-alginate films had good mechanical properties. Antioxidant activity assay through  fixed reaction time method  using DPPH radical (α,α-difenil-β- pikrilhidrazil) resulted in good percentage of radical scavenging activity (%RSA) from the films. The E3 films which contain 1% eugenol has 55.99% of  RSA value in 96 hours.